Effect of Distillation Tank Density and Storage Time on the Quality and Chemical Composition of Cajuput Oil - Satrian Nur Alam; Rini Pujiarti; Kasmudjo Kasmudjo (Masyarakat Peneliti Kayu Indonesia, 2019)
Cajuput oil is a commodity of non-timber forest product which is needed and potential to be developed in Indonesia. Therefore, further research on the factors of production and post-production are needed to produce optimum quality. In this study, the leaves of cajuput (Melaleuca cajuputi Powell) were distillated by water-steam distillation. This study evaluated effects of distillation tank density (60%, 70%, and 80%) and oil storage time (0 month, 1 month, 2 months, and 3 months) on physicochemical properties and chemical compositions of cajuput oils. The results showed that cajuput oils had a specific gravity of 0.915 0.923; optical rotation of (-2,10°) (-1,20°); refractive index of 1.463 1.464; solubility in alcohol 1 : 1; cineole contents of 61.18 76.24%; clear to yellowish clear color; distinctive smell of cajuput and in accordance with SNI 06-3954- 2006. The GC-MS analysis identified 24 of chemical components on the cajuput oils with main components were 1,8-cineole, α-pinene, and β-caryophylene. Tank density 70% to 80% with the oil storage time up to 3 months still gives the optimum quality and chemical compositions.